Changes in neonatal morbidity after rcog guideline 44 for preterm prelabour rupture of membranes. (7th June 2011) - Oswald, N; Anwar, Z; Mackenzie, F; Lilley, C
Abstract : Introduction: The RCOG published Guideline 44 in November 2006 for the management of preterm prelabour rupture of membranes, recommending delivery at 34 weeks. Concern was raised that this may have had a detrimental effect on neonatal morbidity. Objective: Assess the impact on neonatal admissions following introduction of Guideline 44. Methods: Retrospective review of singleton preterm deliveries, 34–36+6 weeks with PPROM: pre-guideline (1 April 2005–31 March 2006) and post-guideline (1 April 2008–31 March 2009). Case note review of NNU admissions. Results: Pre-guideline: 5155 deliveries; 50 pre-term following PPROM; 17 NNU admissions. Post-guideline: 5694 deliveries; 52 pre-term following PPROM; 14 NNU admissions. Conclusion: Implementing the recommendation to deliver women with PPROM at 34 weeks does not appear to cause an increase in NNU admissions, however those admitted have a greater morbidity. Further information will be attained by reviewing all women with PPROM over the study periods.